Perspectives and factors influencing healthy aging among older adults and caregivers in Lishui, China: a mixed-method study - Jianhua, Chen (2025)
Healthy aging (HA) is increasingly recognized as a critical objective in addressing the challenges of global aging populations. This study examines the status, determinants and perspectives of HA among older adults in mountainous regions of Lishui China, thereby addressing an existing research gap. A mixed-methods exploratory sequential design was employed across two phases. Phase I aimed to determine the prevalence of HA and its associated factors. A cross-sectional survey was conducted in Liandu District using a multicentre stratified cluster sampling method. Data were collected from 389 participants (99.7% response rate) through structured questionnaires incorporating the healthy aging index (HAI), sociodemographic variables, lifestyle behaviours, self-perceived healthy aging (SPHA), and eight validated instruments measuring health, environmental and individual-environment (IE) interactions. Data was analyzed using SPSS version 27.0 with linear regression to identify factors associated with HA. The mean HAI score was 136.5 (SD = 18.22), with 65.5% of respondents classified as having a high level of HA. Thirteen factors were significantly associated with HA scores (p < 0.05). Protective factors included economic independence, medical insurance, physical activity, good self-rated health, basic psychological need satisfaction (BPNS) competence, community participation, social support, HSM-consciousness, HSM-behaviour, and SPHA. Risk factors were alcohol consumption, depression, and perceived barriers to health promotion activities. Phase II involved in-depth interviews with 36 older adults and 26 informal caregivers. Thematic analysis revealed four themes: (1) perceptions of HA, including lived experiences, dependencies, and consequences of unmet needs; (2) influencing factors, categorized as facilitators, barriers, and fate-related elements; (3) changes following the common prosperity agenda, such as improved health, living conditions, and trust in government, though some gaps persisted; and (4) recommendations for strengthening HA through individual, environmental, and IE interaction-based strategies. Findings highlight the multidimensional and dynamic nature of HA, shaped by sociodemographic, individual, environmental, cultural, and historical influences. Importantly, perspectives from both older adults and caregivers underscore the need for culturally relevant, community-sensitive strategies. In conclusion, this research provides an integrative perspective on HA in the mountainous communities, highlighting the necessity for targeted, multi-level interventions that address local challenges while supporting the physical, psychological, social, and environmental well-being of older adults